Vliv eura na export ČR (anglicky) - Jurečka, Peter (2007)
This diploma thesis deals with the impact of real exchange rate volatility on real export of the Czech Republic. In the first part, theoretical aspects of this relationship are examined, explaining both - positive and negative ? effects on bilateral and aggregate trade flows. Further on, empirical data and econometric tools are employed to capture the relationship between real export and its main determinants for the case of Czech Republic in the past decade. After the brief theoretical introduction to time series econometrics, the particular export demand model is proposed and various cointegration techniques are explained and applied to examine the long-run equilibrium but also short-run dynamics.